Statistical Reporting as the Basis for Statistical Monitoring of Innovation - V. P. Panteleiev (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The aim of the article is to use the system approach to analysis of the official statistical observation of company innovation in Ukraine. Legal framework for the statistical survey of innovation in Ukraine is highlighted. The role of statistical reporting in the statistical survey of innovation is discussed. An extended review of definitions of “innovation”, “innovation activities”, “innovative products” and “innovating entities” in various regulatory acts of Ukraine is made. The content of reporting forms for the official statistical survey of company innovation in Ukraine, used in 2003–2016, is shown. The indicators contained in various forms of statistical reports on innovation are given, conclusions are made.